The Significance of the Ascension of Christ and Its Implications for Worship - Budianto Lim (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The observance of the Ascension of Christ is not really a prime celebration in most Protestant churches. Even examples of congregational practices related to the celebration of Ascension Day throughout Christian worship history are scarce. Most Christians go through this celebration without much consideration on how the ascended Christ influences life in the here and now. Most would probably view Christ as the heavenly king and unconsciously ignore the fact that Christ ascended as the high priest who can empathize with his people. Although Indonesia treats this Christological event as a public holiday, the preparation leading to the celebration is not as significant as other commemorations like Good Friday, Easter, and Christmas. The consequence is that Christians do not have a meaningful worship experience that may inspire them to endure the life of daily discipleship. Thus, the focus of this article is on understanding the significance of Christ’s ascension and how the church can celebrate Ascension Day in ways that help Christians live according to Christ’s teaching and hope for the future. This article will reconsider the biblical and theological foundations of the ascension to develop worship that strengthens the identity of Christians for daily discipleship.